2014
DOI: 10.1007/5584_2014_20
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inspiratory Muscle Training on Resistance to Fatigue of Respiratory Muscles During Exhaustive Exercise

Abstract: The aim of this study was to assess the effect of inspiratory muscle training (IMT) on resistance to fatigue of the diaphragm (D), parasternal (PS), sternocleidomastoid (SCM) and scalene (SC) muscles in healthy humans during exhaustive exercise. Daily inspiratory muscle strength training was performed for 3 weeks in 10 male subjects (at a pressure threshold load of 60% of maximal inspiratory pressure (MIP) for the first week, 70% of MIP for the second week, and 80% of MIP for the third week). Before and after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Taken together however, in combination with those of Held and Pendergast (27), these studies suggest that RMT improves ventilatory efficiency, which may partially account for improvements in performance. Further, it is possible that improved ventilatory efficiency may contribute to enhanced resistance to respiratory muscle fatigue following RMT, as documented by recently by Segizbaeva et al (66).…”
Section: Discussionmentioning
confidence: 83%
“…Taken together however, in combination with those of Held and Pendergast (27), these studies suggest that RMT improves ventilatory efficiency, which may partially account for improvements in performance. Further, it is possible that improved ventilatory efficiency may contribute to enhanced resistance to respiratory muscle fatigue following RMT, as documented by recently by Segizbaeva et al (66).…”
Section: Discussionmentioning
confidence: 83%
“…Chest expansion showed no statistical change after the sessions of IMT. We found no reference in relation to the measurement of thoracic cirtometry before or after IMT [6,7,9,10,28].…”
Section: Discussionmentioning
confidence: 74%
“…Several studies used a load of 50 % of MIP, applied in 1 set of 30 repetitions, with the apparent purpose of increasing inspiratory muscle strength with no association with resistance gain [7,[9][10][11][12]. Moderate to high loads with a high number of repetitions (60-80 % MIP, 60 repetitions) can be associated with an increase in both inspiratory muscle strength and resistance [28]. In order to evaluate the influence of IMT on respiratory muscle strength and aerobic capacity, we proposed two different protocols (with different loads and frequencies) for indoor soccer players.…”
Section: Discussionmentioning
confidence: 99%
“…This was consistent with the observation of several studies which showed that inspiratory muscle training increased inspiratory muscle strength, delayed IMF during exhaustive exercise, and improved maximal performance significantly. 27 Volianitis has shown that RMT in lightweight oarswomen produced significant increases in PImax, decreased IMF, and improved rowing performance during a 6-minute all-out of effort and 5000m race. 28 Some studies have suggested that even cardiovascular exercise (aerobic exercise) training protects athletes from the effects of RMF.…”
Section: Discussionmentioning
confidence: 99%